Measurement of aortic regurgitation by Doppler echocardiography. Issue 1 (January 1986) - Zhang, Y; Nitter-Hauge, S; Ihlen, H; Rootwelt, K; Myhre, E
Abstract : In an attempt to develop a new approach to the non-invasive measurement of aortic regurgitation, transmitral volumetric flow (MF) and left ventricular total stroke volume (SV) were measured by Doppler and cross sectional echocardiography in 23 patients without aortic valve disease (group A) and in 26 patients with aortic regurgitation (group B). The transmitral volumetric flow was obtained by multiplying the corrected mitral orifice area by the diastolic velocity integral, and the left ventricular total stroke volume was derived by subtracting the left ventricular end systolic volume from the end diastolic volume. The aortic regurgitant fraction (RF) was calculated as: RF = 1 - MF/SV. In group A there was a close agreement between the transmitral volumetric flow and the left ventricular total stroke volume, and the difference between the two measurements did not differ significantly from zero. In group B the left ventricular total stroke volume was significantly larger than the transmitral volumetric flow, and there was good agreement between the regurgitant fractions determined by Doppler echocardiography and radionuclide ventriculography. Discrepancies between the two techniques were found in patients with combined aortic and mitral regurgitation or a low angiographic left ventricular ejection fraction (less than 35%). The effective cardiac output measured by Doppler echocardiography accorded well with that measured by the Fick method. Doppler echocardiography provides a new and promising approach to the non-invasive measurement of aortic regurgitation.